Enhancement of Photon Absorption on BaxSr1-xTiO3 Thin-Film Semiconductor Using Photonic Crystal - Abd. Wahidin Nuayi; Husin Alatas; Irzaman S. Husein; Mamat Rahmat (International Journal of Optics)
Enhancement of photon absorption on barium strontium titanate (BaxSr1-xTiO3) thin-film semiconductor for mole fraction x=0.25, 0.35, 0.45, and 0.55 using one-dimensional photonic crystal with defect was investigated experimentally. The thin film was grown on transparent conductive oxide (TCO) substrate using chemical solution deposition method and annealed at 500°C for 15 hours with increasing rate of 1.6°C/min. From optical characterization in visible spectrum it was found that the average absorption percentages are 92.04%, 83.55%, 91.16%, and 80.12%, respectively. The BST thin film with embedded photonic crystal exhibited a relatively significant enhancement on photon absorption, with increasing value of 3.96%, 7.07%, 3.04%, and 13.33% for the respective mole fraction and demonstrating absorbance characteristic with flat feature. In addition, we also discuss the thin-film properties of attenuation constant and electrical conductivity.